Analisis Pengaruh Modal Dan Biaya Produksi Terhadap Pendapatan Usaha Mikro, Kecil Dan Menengah Depot Isi Ulang Air Minum Di Kota Palangka Raya - Dicky Perwira Ompusunggu; Leli Astuti Gulo (Journal of Management and Social Sciences, 2023)
This study aimed to analyze the effect of capital and production costs on the income of micro, small and medium enterprises at the city of Palangkaraya drinking water filling depot. This research will provide a clearer picture of the factors that affect the income of a drinking water-filling depot business. The quantitative approach to multiple regression analysis is a method of conducting research by focusing on the relationship between variables using quantitative data. From this study, capital and production costs significantly influence the income of micro and SME enterprises at drinking water filling depots in Palangkaraya City. Revenue increases when capital and production costs increase; income decreases when it decreases. Together, these two effects explain 60.3% of income inequality. Suggestions for future researchers are to expand the scope of their research by considering other factors that can affect the income of micro, small and medium enterprises (UMKM) drinking water stations, such as Business location, product quality, and marketing strategy.